Peninjauan Hukum Menurut Hukum Adat Kampar: Sumbangan dalam Mewujudkan Hukum yang Responsif - Haniah Ilhami (Jurnal Konstitusi, 2022)
The development of Indonesian constitutional law, especially judicial review, is influenced by the liberal continental and Anglo-Saxon legal systems. Meanwhile, Kampar customary law already has a legal review system with the philosophy "Adat tali bapilin tigo, tigo tunggku sajoghangan" with the ultimate goal "Adat bersendi syara’, syara’ bersendi Kitabullah". This paper examines legal review under Kampar customary law, using qualitative analysis, historical approaches, and the identification of unwritten laws. The concept presented is based on the concept of reasoning for the formation of a norm system that combines three elements, namely religion, custom, and government (the Trinity). The coherence of this concept should be a new offering in the expanded power of judicial review. The review of the legal norms should extend to the level of the ethical review. The expansion can be done by adopting the concept of legal testing reasoning according to Kampar customary law according to the moral system.